An evaluation of a high‐pressure 11CO carbonylation apparatus. (27th March 2015) - Dahl, Kenneth; Itsenko, Oleksiy; Rahman, Obaidur; Ulin, Johan; Sjöberg, Carl‐Olof; Sandblom, Peter; Larsson, Lars‐Anders; Schou, Magnus; Halldin, Christer
<x xml:space="preserve">Abstract</x> [11C]Carbon monoxide (11CO) is a versatile building block for the synthesis of Positron Emission Tomography (PET) radioligands. However, the difficulty of trapping 11CO in a small solvent volume has limited its utility. We here report an evaluation of a simple, fully automated high‐pressure synthesizer prototype for the use in 11C‐carbonylation reactions. [11C]Carbon monoxide was easily prepared by online reduction of [11C]carbon dioxide using either Mo(s) or Zn(s) as the reducing agent. The conversion yield of 11CO was >99% when zinc was used as the reducing agent, and the corresponding value for Mo was approximately 71%. When the Zn or Mo column was constantly kept under inert atmosphere, no significant decrease in reducing properties was observed for more than 100 11CO productions. However, in our hands, Mo reductant was much easier to service. A total of nine functional groups were successfully radiolabeled using the 11CO synthesizer prototype. All measured radiochemical yields exceeded 37%, and the 11CO trapping efficiency was generally above 90%, except for the Suzuki coupling where the trapping efficiency was 80%. This high‐pressure synthesizer using [11C]carbon monoxide as the labeling precursor is easy to operate allowing for 11C‐carbonylation reactions to be performed in a high yield and in a routinely fashion.